Comparison Between Urothelial and Non-Urothelial Urethral Cancer - Wenzel, Mike; Deuker, Marina; Nocera, Luigi; Collà Ruvolo, Claudia; Tian, Zhe; Shariat, Shahrokh F.; Saad, Fred; Briganti, Alberto; Becker, Andreas; Kluth, Luis A.; Chun, Felix K.H.; Karakiewicz, Pierre I. (Frontiers in Oncology, 2021)
Background: To test the effect of variant histology relative to urothelial histology on stage at presentation, cancer specific mortality (CSM) and overall mortality (OM) after chemotherapy use, in urethral cancer. Materials and Methods Within the Surveillance, Epidemiology and End Results (2004–2016) database, we identified 1,907 primary variant histology urethral cancer patients. Kaplan-Meier plots, Cox regression analyses, cumulative incidence-plots, multivariable competing-risks regression models and propensity score matching for patient and tumor characteristics were used. Results: Of 1,907 eligible urethral cancer patients, urothelial histology affected 1,009 (52.9%) vs. squamous cell carcinoma (SCC) 455 (23.6%) vs. adenocarcinoma 278 (14.6%) vs. other histology 165 (8.7%) patients. Urothelial histological patients exhibited lower stages at presentation than SCC, adenocarcinoma or other histology patients. In urothelial histology patients, five-year CSM was 23.5% vs. 34.4% in SCC (Hazard Ratio (HR) 1.57) vs. 40.7% in adenocarcinoma (HR 1.69) vs. 43.4% in other histology (HR 1.99, p<0.001). After matching in multivariate competing-risks regression models, variant histology exhibited 1.35-fold higher CSM than urothelial. Finally, in metastatic urethral cancer, lower OM was recorded after chemotherapy in general, including metastatic adenocarcinoma and other variant histology subtypes, except metastatic SCC. Conclusion: Adenocarcinoma, SCC and other histology subtypes affect fewer patients than urothelial histology. Presence of variant histology results in higher CSM. Finally, chemotherapy for metastatic urethral cancer improves survival in adenocarcinoma and other variant histology subtypes, but not in SCC.